Addressing identity conflict in multicultural human resource management in Indonesia - Fitri, Sari (Institute of Computer Science (IOCS), 2025)
Identity conflicts based on ethnicity, religion, race, and inter-group (SARA) have become a significant challenge in human resource management (HR) in Indonesia, especially in the context of multiculturalism. Identity politics that seep into organizations often create polarization that disrupts harmony and work productivity. This study uses a descriptive qualitative approach with a case study method in several multicultural organizations in Indonesia. Data collection in this study was carried out through a literature review that included a study of various organizational policies related to diversity and inclusion, as well as an analysis of the results of previous studies on human resource management (HR) in the context of multiculturalism. This approach aims to understand the main factors that influence identity conflict in the workplace, including the role of policies, organizational dynamics, and relevant management strategies. The study found that identity conflict in the workplace is triggered by several main factors, namely external identity politics that affect the internal dynamics of the organization, discrimination based on SARA, and leadership that is biased towards certain groups. The impacts of this conflict include decreased productivity, increased turnover rates , and decreased employee welfare. To address this conflict, organizations that successfully implement inclusive leadership, anti-discrimination policies, meritocratic systems, and diversity training are able to create a more harmonious and inclusive work environment. In addition, implementing a work culture that values diversity has also proven effective in reducing polarization in the workplace